2016
DOI: 10.1515/noise-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

A soundscape approach to exploring design strategies for acoustic comfort in modern public libraries: a case study of the Library of Birmingham

Abstract: Taking the soundscape approach to a study of the Library of Birmingham, this paper explored acoustic comfort in modern public libraries and measured the quality of the perceived sound environment, focusing on the appropriateness of the spatial organisation to facilitate users’ activities of reading and writing. The research involved four groups of participants taking soundwalks which provided data at four main floors in the Library, identifying types of sounds, measuring sound pressure levels and evaluating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 12 publications
0
36
0
2
Order By: Relevance
“…Although the use of sound absorbing materials is well known for the improvement of acoustic comfort in closed rooms/buildings (Battaglia, 2014;Xiao and Aletta, 2016;Thomas et al, 2018), less is known about the use of such materials for the improvement of acoustic comfort for residents of housing complexes with shared inner yards (Taghipour et al, 2019c). Within other exterior spaces of the urban layout, facade absorption has been found to affect the acoustic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of sound absorbing materials is well known for the improvement of acoustic comfort in closed rooms/buildings (Battaglia, 2014;Xiao and Aletta, 2016;Thomas et al, 2018), less is known about the use of such materials for the improvement of acoustic comfort for residents of housing complexes with shared inner yards (Taghipour et al, 2019c). Within other exterior spaces of the urban layout, facade absorption has been found to affect the acoustic performance.…”
Section: Introductionmentioning
confidence: 99%
“…While the definition of soundscape has been standardized (ISO 12913-1, 2014), the term "acoustic comfort" has a broader and more colorful definition in the literature (Taghipour et al, 2019b). In many studies, the improvement of acoustic comfort has been presented as the general improvement of acoustics, measured in objective acoustical and/or room acoustical parameters (such as lower SPL) (Xiao and Aletta, 2016;Thomas et al, 2018). Other studies have used a subjective evaluation of the acoustic comfort (Yang and Kang, 2005;Kang and Zhang, 2010;Battaglia, 2014;Taghipour et al, 2019b), where acoustic comfort was found to be related to the SPL (Yang and Kang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While the concept has attracted an increasing interest in urban studies, and outdoor environments more in general, it also applies to indoor contexts, particularly when they serve "public" functions, like service buildings, public libraries, transportation hubs, restaurants, or other commercial facilities [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Designers could also update the needs of people to acoustic indoor environment using public spaces because needs of people for acoustic requirements of space could be higher for their key activity e.g. for 'reading and thinking' than for 'interacting and communicating' in library [27]. Participatory measurements of noise levels can be a useful approach to involve inhabitants, business people, school people to increase their awareness about noise and noise reduction measures in Tirana.…”
Section: Discussionmentioning
confidence: 99%